A retrospective, non-interventional, electronic medical record based real world data analysis in patients suffering from pruritus in type 2 diabetes mellitus - Kalra, Sanjay; Mittal, Asit; Vyas, Kapil; Rathod, Roheet Mohan; Rathod, Rahul; Bhagat, Seema Vikas; Mane, Amey; Hawelia, Dinesh Kumar; Basu, Utsa; Shah, Snehal (International Journal of Research in Dermatology, 2022)
Background: There is limited data highlighting the association of pruritus with Type 2 Diabetes Mellitus (T2DM). This was the first Electronic Medical Record (EMR) based real-world observational study on the demographics, clinical characteristics, associated risk factors and treatment(s) of pruritus in T2DM in India. Methods: EMR data of patients was retrospectively analysed with a baseline (V1) visit and two or more follow-up visits between June 2014-December 2019. Results: Majority of patients were 40-64 years old and mainly females (57%). Body mass index and co-morbidity data indicated a trend of obesity and hypertension. Observed HbA1c values were high (mean value of 9%). Majority of the patients were on hydroxyzine. Miconazole, fluconazole and corticosteroids were prescribed in 40% patients. Correlation between HbA1c levels with clinical pruritus was noted. Conclusions: Management of glycaemia along with timely dermatological intervention is needed for pruritus relief in T2DM, the use of antihistamines; in particular, hydroxyzine, should be further evaluated.